From Rhetoric to Interculturality. Some reflections on the contributions of Bartolomé de las Casas - Zuchel, Lorena; Krupecka, Iwona (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Writing in favor of the rhetoric, Las Casas was actually searching for a new anthropological model that would be different both from the elite humanism and from the Erasmian voluntarism. We would like to emphasize this attitude in the light of Las Casas’ practical objectives, which is to prevent from further homicide and to guarantee an unconditioned freedom to the Indians in every aspect of their social life. We will refer to this revolutionary attitude which is based on the theories of Aristotle and St. Thomas, but is also capable of overshadowing them in defense of the humanity itself and human values. The most important point of Las Casas’ theory is the recognition of the right and ability of every community to have an autonomous way of governing. For that reason, we argue, his writings can be interpreted as an important contribution to the question of the recognition of the Other, and as the theoretical starting point for the intercultural philosophy as well.
Keywords: Bartolomé de las Casas; rhetoric; interculturality; humanism; recognition